Pamanime ning lacatan malutu (separate chaff from grain) multi-dimensional assesment of agrarian cultural landscape values a case study of Duman agricultural landscape of Barangay Sta. Monica - Cunanan, Joshua S. (College of Architecture, University of the Philippines Diliman, 2018)
The concept of Cultural Landscape emerged in the 1992 World Heritage Convention, becoming the first instrument in safeguarding and providing recognition to cultural landscapes, defined as cultural properties representing the combined works of nature and man (World Heritage Committee, 1992). Recent related literature reveal that most cultural landscapes are assessed according to their Outstanding Universal Values, which unfortunately results in the deprioritization of certain landscapes, including rural agrarian areas like those in the Philippines. Thus, the study focuses on the need to develop a comprehensive assessment tool, tailored specifically for the agrarian cultural landscape. Five evaluative dimensions- ecological, production, economic system, cultural, and social values- were adopted from analyzing cultural landscape assessment theories. Aiming to generate a visual and quantifiable measure of assessing its acceptability, the tool was applied to a specific site located in the Duman Agricultural Landscape of Barangay Santa Monica, Municipality of Santa Rita, Pampanga. The proposed Agrarian Cultural Landscape Values Assessment Tool was found to be effective not only in determining the full values of agrarian cultural landscapes, but also in assisting cultural agencies and related research fields in considering the different landscapes in the country.